Condilomata Lata as Clinical Manifestation of Secondary Syphillis In Pregnancy: Study Case Report - A A Ayu Adisti Nina Yuniandari; Diana Wijayanti (Syntax Corporation Indonesia, 2022)
The bacterium Treponema pallidum, which causes the infectious disease syphilis, assaults people. Syphilis is a chronic, systemic disease that can affect all regions of the body, can remain dormant for years, is communicable, and can be treated. One of the symptoms of secondary syphilis is condyloma lata. The most typical location is in warm, muggy climates. We describe case G1P0A0, a 29-year-old woman who is 28 weeks pregnant. The patient's main complaint upon arrival was that he had been developing larger and more frequent warts on his genitalia for the past month. The patient, who has only ever been married once, denies having had any previous relationships with men other than her husband. The patient's husband allegedly had sex with prostitutes without wearing a condom in 2021 and admitted to having previously experienced genital injuries in November of that same year but choosing not to seek medical attention. Her vital signs and overall status were within normal ranges, and she appeared to be in good health. Multiple 2 cm grey circular plaques with a localized status were found on the labia majora. A VDRL serological examination was performed as a follow-up examination on June 16; the results were reactive. At 28 weeks of gestation, the patient was diagnosed with secondary syphilis in the form of condyloma lata based on the history, physical examination, and supportive examination. Erythromycin 500 mg 4x1, paracetamol 500 mg for pain, and a 0.9% NaCl compress were administered to the patient as treatment. Reevaluated after the first month. The VDRL test yielded a titer of 1: 16 and the complaints of lumps in the genitalia had vanished. The patient is advised to have the exam redone in three, six, twelve, and twenty-four months.